2018
DOI: 10.1111/aej.12304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different protocols of eugenol removal on the bond strength between the fibre post and root dentin

Abstract: The aim of this study was to evaluate the bond strength between the fibre post and root dentin after different cleaning protocols to remove eugenol from dentin. The residues and elemental composition of dentin were analysed using SEM and EDS. Bovine incisor roots were obturated with eugenol-based sealer. The post space was prepared, and the roots were divided into the following groups according to the cleaning protocol: unfilled (negative control), saline solution (positive control), 70% ethanol, acetone and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
(61 reference statements)
1
9
0
1
Order By: Relevance
“…Our results also indicate that the use of isopropyl alcohol, either by immersion in an ultrasonic bath or by washing, in combination with sandblasting, is the best way to remove any eugenol residues, thus significantly enhancing the retention (Table 3). This finding is in agreement with de Oliveira et al, who observed the efficacy of different cleaning protocols/agents on the bond strength of dental fiber post and root dentin (de Oliveira et al, 2019). After testing saline solution, acetone, 70% ethanol, and 70% isopropyl alcohol, it was found that with the two alcohols, higher bond strengths were obtained.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also indicate that the use of isopropyl alcohol, either by immersion in an ultrasonic bath or by washing, in combination with sandblasting, is the best way to remove any eugenol residues, thus significantly enhancing the retention (Table 3). This finding is in agreement with de Oliveira et al, who observed the efficacy of different cleaning protocols/agents on the bond strength of dental fiber post and root dentin (de Oliveira et al, 2019). After testing saline solution, acetone, 70% ethanol, and 70% isopropyl alcohol, it was found that with the two alcohols, higher bond strengths were obtained.…”
Section: Discussionsupporting
confidence: 92%
“…The excessive use of acetone may negatively affect the bond strength as a result of collagen fiber collapse. 33 However, this assumption warrants further investigation.…”
Section: Discussionmentioning
confidence: 94%
“…Pure acetone (propanone) protocol also decreased the dentin microhardness but was not comparable to amyl acetate. It may be attributed to dentin dehydration since acetone dehydrates the specimens during the microscopic analysis 12 . Nevertheless, 95% ethanol showed lower deleterious effects on dentin 28 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 95% ethanol (ET) is a hydrated polar solvent with a strong molecular bonding with water 1,7,8 . Thus, the miscibility between them is low, the persistence of sealer residues after cleansing using ET on dentin surface is high, and therefore, it is not the most effective method 8,12,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation